2021
DOI: 10.1128/aac.02420-20
|View full text |Cite
|
Sign up to set email alerts
|

A Leucyl-tRNA Synthetase Inhibitor with Broad-Spectrum Antimycobacterial Activity

Abstract: Global infections by non-tuberculous mycobacteria (NTM) are steadily rising. New drugs are needed to treat NTM infections, but the NTM drug pipeline remains poorly populated and focused on repurposing or reformulating approved antibiotics. We sought to accelerate de novo NTM drug discovery by testing advanced compounds with established activity against Mycobacterium tuberculosis. 3-aminomethyl 4-halogen benzoxaboroles, a novel class of leucyl-tRNA synthetase inhibitors, were recently discovered as active again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 55 publications
2
35
0
Order By: Relevance
“…Recently, we reported that the antituberculosis 4-halogen benzoxaborole EC/11770 ( Fig. 1 ) is active against M. abscessus in vitro and in vivo in a mouse infection model ( 14 ). Here, we asked whether the anti-Gram-negative, nonhalogenated benzoxaborole epetraborole ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we reported that the antituberculosis 4-halogen benzoxaborole EC/11770 ( Fig. 1 ) is active against M. abscessus in vitro and in vivo in a mouse infection model ( 14 ). Here, we asked whether the anti-Gram-negative, nonhalogenated benzoxaborole epetraborole ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…We first measured the MIC of this compound against our screening strain M. abscessus subsp. abscessus Bamboo ( 15 ) in Middlebrook 7H9 medium using 96-well plates, as previously described ( 14 ). Surprisingly, epetraborole showed activity similar to that of the antitubercular EC/11770 ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, EC/11770 inhibited the growth of the Mab biofilm in vitro model and showed effective in vivo efficacy in the NOD SCID mice lung infection model. Fortunately, EC/11770 showed low-resistant mutant frequency, and leucyl-tRNA synthetase was confirmed as its target ( Ganapathy et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%